Wind watchers [book with audioplayer] - Archer, Micha ([Library Ideas, LLC], 2025)
"Seasons come and go, and the wind wafts its way through them all. This delights a family of children, and when they ask the wind, "How will you blow today?" they get a kick out of not knowing what answer they'll get. Will the wind send gentle breezes that tickle and delight, cooling them off on hot days? Or strong gusts that knock their hats off and send them running inside on stormy days? One thing is for certain to our wind watchers--the wind is an always-changing wonder and constantly takes their breath away!" --